The CORRELATION BETWEEN ENGLISH SPEAKING COMMUNITY LEVEL AND STUDENTS’ SPEAKING PERFORMANCE IN PUBLIC SPEAKING CLASS - Falahiyah, Fillah (RETAIN, 2021)
Speaking is an essential skill that is needed by EFL learners. It has been taught in Indonesia for a long time as a foreign language. However, most students get difficulties in learning especially students at university level because they are not confident to speak in front of people. They need to practice more not only inside but also outside the class. University offers Public Speaking course to help students achieve their speaking skill. Moreover, to facilitate students in achieving their speaking skill, some universities offer a speaking community to help students practice speaking outside the class. Therefore, this study aimed to investigate the correlation between English Speaking Community level offered by the university and students’ speaking performance in Public Speaking class. The design of this study is correlational study. There are 27 English Education students on the second semester from 5 groups of ESC in State University of Surabaya as the participants of this study. The data obtained through the questionnaire, observation, questionnaire, and the speaking test and analyzed using Pearson Product Moment in SPSS. The result shows that there is correlation between English Speaking Community level and students’ speaking performance. Thus, students’ can improve their speaking performance by joining ESC offered by the department. Keywords: English Speaking Community, Speaking Performance, Public Speaking Class